ARTIFICIAL INTELLIGENCE AND HUMAN VALUES IN THE PROCESS OF GLOBAL TRANSFORMATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the impact of artificial intelligence on social life, human thinking, and spiritual and moral relations during the process of global transformation. The study substantiates that artificial intelligence is not only a tool for technological progress but also a crucial factor testing human values. The article highlights the role of values such as human honor and dignity, freedom, justice, responsibility, transparency, and solidarity in the process of creating and applying artificial intelligence.